Investigation of Radiation Absorption Behavior of Banana Leaves and Onion: A Cost-Effective Way of Radiation Protection - Arpita Datta; Alpana Goel; Shreya Singh (International Journal of Nuclear Security, 2025)
Shielding of nuclear radiation is an important component of radiation safety aiming to reduce the exposure of ionizing radiation to radiation workers. In the present work, beta and gamma radiation absorption properties of various environmentally friendly natural materials such as onion, banana leaf, and banana stem were investigated with a view to understand their radiation shielding capability. Pure beta source 90Sr–90Y and gamma sources such as 241Am, 137Cs and 60Co were used to study the attenuation of beta and gamma radiation using these natural materials. Intensity of the emitted radiation was measured by placing the circular disc of these materials with various thicknesses between a radiation detector and radioactive source. The mass attenuation coefficient (µm = µ/ρ), linear attenuation coefficient (μ) for beta and gamma rays, and half value thickness (cm) were calculated for onion, banana leaf, and banana stem. The mass attenuation coefficient (µm) and linear attenuation coefficient (μ) of these materials were compared with other shielding materials such as aluminum, polyethylene, and copper, and the μm and μ values of the onion, banana leaf, and banana stem were found to be close to the values of polyethylene for gamma radiation. The results also indicated that these natural materials could be good for shielding against beta radiations. This study can be used to comprehend the radiation shielding effectiveness of onion, banana leaf, and banana stem fibers for the production of composite materials.
Keywords: Radiation Protection; Beta-gamma radiations shielding; Banana leaf and stem; Onion and attenuation coefficients.